(untitled) (KULT_online, 2017)
The volume Müll. Interdisziplinäre Perspektiven auf das Übrig-Gebliebene, edited by Christiane Lewe, Tim Othold, and Nicolas Oxen discusses things-that-remain from a cultural perspective. Assuming that material remains are the result of socio-cultural attributions, the contributions focus on phenomena such as representations of garbage on television, gender and dirt, building recycling, self-storage, and artistic negotiations of rubbish. Serving as a common intersection of the case studies, it turns out that the volume tries to counteract the devaluations of remains as they are conventionally attributed. However, the perspective of literary study is found to be absent.